Costs and Benefits of More Efficient Irrigation Systems for Florida Chipping Potato Production - Jenna Rogers; Tatiana Borisova; Lincoln Zotarelli; Kelly Grogan; Jeffrey Ullman; Jessica Bertine; Kelly Morgan (EDIS)
The goal of this 11-page fact sheet is to help producers and other interested parties understand how alternative irrigation systems can affect economic outcomes in agricultural operations. We used chipping potato production in the Hastings area in northeast Florida as an example to discuss factors to consider when selecting an irrigation system. Written by Jenna Rogers, Tatiana Borisova, Lincoln Zotarelli, Kelly Grogan, Jeffrey Ullman, Jessica Bertine, and Kelly Morgan, and published by the UF Department of Food and Resource Economics, September 2014.